ANALIZA WYBRANYCH ZANIECZYSZCZEŃ POWIETRZA W 2018 R. NA TERENIE BIELSKA-BIAŁEJ - GÓRA, DARIUSZ (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2019)
Chemical composition of polluted atmospheric air has a negative impact on human health as well as animals, water and soil. In effect it causes respiratory system disease, blood system disease and cancers. Children and elderly people are among the most endangered as their immune system is weak. It is estimated that every year in Poland 45000 people die as a result of polluted air. On a global scale the number rises to 7 million people. The aim of this elaboration is to present the concentration of chemical elements and particles, such as: suspended dust PM10 and PM2.5, nitro dioxide sulphur and benzo(a)pyrene, and to prove their negative impact on the human body. The article includes data from the Provincial Inspectorate for Environmental Protection in Katowice, Delegature in Bielsko-Biała. The next stage was to prepare appropriate graphs that show the concentrations of elements and chemical compounds in the air in individual months in 2018. The conducted analysis showed that the average annual PM2.5 dust concentration was 36 μg/m3, PM10 suspended dust 37 μg/m3, benzo(a)pyrene 4.47 ng/m3 and nitrogen oxides 62 μg/m3. In order to improve the sanitary state of the atmospheric air in the city of Bielsko-Biała and other areas with a high degree of urbanization, first of all reduce the sources of low emissions, i.e. emission of harmful dusts and gases from low emitters, which include chimneys, e.g from single-family houses or townhouses. Literature data show that exposure of people to particulate matter, benzo (a) pyrene and nitric oxides is mainly associated with an increased risk of heartbeat, bronchopulmonary and lung cancer and asthma.